Pliocene-Quaternary crustal melting in central and northern Tibet and insights into crustal flow - Wang, Q.; Hawkesworth, C.; Wyman, D.; Chung, S.; Wu, F.; Li, X.; Li, Zheng-Xiang; Gou, G.; Zhang, X.; Tang, G.; Dan, W.; Ma, L.; et al. (Macmillan Publishers Limited, 2016)
There is considerable controversy over the nature of geophysically recognized low-velocity-high-conductivity zones (LV-HCZs) within the Tibetan crust, and their role in models for the development of the Tibetan Plateau. Here we report petrological and geochemical data on magmas erupted 4.7-0.3 Myr ago in central and northern Tibet, demonstrating that they were generated by partial melting of crustal rocks at temperatures of 700-1,050°C and pressures of 0.5-1.5 GPa. Thus Pliocene-Quaternary melting of crustal rocks occurred at depths of 15-50 km in areas where the LV-HCZs have been recognized. This provides new petrological evidence that the LV-HCZs are sources of partial melt. It is inferred that crustal melting played a key role in triggering crustal weakening and outward crustal flow in the expansion of the Tibetan Plateau.